In-vitro Antioxidant and Cytotoxicity Studies of Annona squamosa Linn. (Stamford Journal of Pharmaceutical Sciences, 2010)
n-Hexane, chloroform and methanol soluble extracts of the leaves of Annona squamosa were screened fortheir possible antioxidant activitiy by DPPH free radical scavenging and cytotoxicity by brine shrimp lethalitybioassay. In DPPH radical scavenging assay, methanol soluble extract was found to be the most potent withan IC50 value of 103.5 μg/ml. The amount of total phenolics was also found to the highest in the methanolsoluble extract (283.16 ± 8.90 mg/g), followed by chloroform soluble extract (216.90 ± 4.48 mg/g). Here BHTand ascorbic acid were used as standards with IC50 values 8.2 μg/ml and 25 μg/ml respectively. In the brineshrimp lethality bioassay, the most significant cytotoxicity was observed with chloroform soluble extract withan LC50 of 4.16 μg/ml where vincristine sulphate was used as standard (LC50 0.29 μg/ml).Key Words: Annona squamosa; DPPH; Folin-Ciocalteu Reagent; Phenolic Contents; Brine ShrimpDOI: 10.3329/sjps.v2i1.5813Stamford Journal of Pharmaceutical Sciences Vol.2(1) 2009: 32-36